1991
DOI: 10.1039/ft9918701929
|View full text |Cite
|
Sign up to set email alerts
|

Tin oxide surfaces. Part 21.—Infrared study of the chemisorption of 2,2,2-trifluoroethanol, 1,1,1,3,3,3-hexafluoropropan-2-ol, 1,1,1-trifluoropropan-2-one, 1,1,1,3,3,3-hexafluoropropan-2-one and trifluoroacetic acid on tin(IV) oxide gel

Abstract: The adsorption of trifluoroacetic acid, 1,1,1,3,3,3-hexafluoropropan-2-one, 1,l ,l-trifluoropropan-2-one, 2,2,2-trifluoroethanol and 1,1,1,3,3,3-hexafluoropropan-2-ol on tin(iv) oxide gel has been studied by infrared spectroscopy. Trifluoroacetic acid is adsorbed as both hydrogen-bonded molecular trifluoroacetic acid and surface trifluoroacetate, the former being totally converted into the latter by 533 K. The surface trifluoroacetate decarboxylates by 673 K to give surface trifluoromethoxide. Both of the keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…These include doping with fluoride and metal ions, ,, coupling the films with metal oxide, modifying the substrates, , and treating the films with acid. , Liao et al reported the adsorption and photoreactions of acetic acid on TiO 2 powders . The chemisorption of trifluoroacetic acid (TFA), an acid with strong electron-withdrawing groups, has also been reported . However, the substrate used in that particular study was tin(IV) oxide gel.…”
Section: Introductionmentioning
confidence: 99%
“…These include doping with fluoride and metal ions, ,, coupling the films with metal oxide, modifying the substrates, , and treating the films with acid. , Liao et al reported the adsorption and photoreactions of acetic acid on TiO 2 powders . The chemisorption of trifluoroacetic acid (TFA), an acid with strong electron-withdrawing groups, has also been reported . However, the substrate used in that particular study was tin(IV) oxide gel.…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that a small quantity of water contained in the solvent would initiate the hydrolysis of TBT, in view of the fact that TBT is a highly hydrolyzable material. Besides this, the residual solvent TFA is observed by the CF 3 stretching vibration peak detected at 1197 and 1146 cm –1 . Moreover, the C–C and C–H stretching vibration bands and Ti–O–C band are undetectable in the hydrolyzed precursor.…”
Section: Resultsmentioning
confidence: 94%
“…Besides this, the residual solvent TFA is observed by the CF 3 stretching vibration peak detected at 1197 and 1146 cm À1 . 31 Moreover, the CÀC and CÀH stretching vibration bands and TiÀOÀC band are undetectable in the hydrolyzed precursor. These results demonstrate that the Ti-OR had completely transformed into TiÀOH via the hydrolysis reaction under acid catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the end, some remarks are necessary regarding the described changes in the carboxylate infrared bands during stepwise heating. Simultaneous appearance of more than two of those absorptions is usually ascribed to the existence of carboxylate species interacting in different ways with the solid surfaces (e.g., (11,12)). In the case of unidentate species, two absorptions appear with a large separation due to the essentially single-and double-bond character of the two carbonoxygen bonds.…”
Section: B Reactions Of Adsorbed Species At Higher Temperaturesmentioning
confidence: 99%